Extraction and characterization of hydroxyapatite (HA) from eggshell by precipitation method for bone implant coating: A Case Study - Amiruddin, Ahmad Nazmi; Mat Noor, Fazimah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research study was showed the extraction and characterization of hydroxyapatite (HA) from eggshell by precipitation method for bone implant coating. The eggshell were carried out using wet precipitation method in order to extract hydroxyapatite powder from the eggshell. Various parameters were used through the calcination process such as the first calcination process will be implemented at 900 °C for 1 hour while the second calcination process will be run at 1000 C within 2 hours. The different of pH value also used as parameters. The characterization of hydroxyapatite (HA) from eggshell powder have been conduct through scanning electron microscopy (SEM), X-Ray diffraction (XRD) and Fourier transform (FTIR). By SEM, the microstructure of hydroxyapatite (HA) based on different pH and calcination temperature could be analyse. The purpose use of XRD is to categorize the crystalline material and define the unit cell. From XRD, SEM and FTIR findings, the effect of pH and effect of calcination temperature are determined. For FTIR, the elements and arrangement of molecules can be define. The result of analysis are retrieve from the previous research. According to the past research, pH value and calcination temperature are the strong influence on the SEM morphology. By comparing among the previous research, precipitation method the most method that applied and source of material from eggshell wastage. Thus, hydroxyapatite (HA) from eggshell could be prove by precipitation method for bone implant coating.